PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI KELAS V UPTD SD NEGERI 27 PEUSANGAN - Islami, Najiwa; Nurmina; Agustisa, Mutia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the improvement of students' explanatory text writing skills, teacher activities, student activities, and students' responses through the implementation of the Think Talk Write (TTW) learning model in Grade V students at UPTD SD Negeri 27 Peusangan. This research was motivated by the low level of students' explanatory text writing skills and their lack of active participation in the learning process. Therefore, an appropriate learning model was needed to improve students' writing abilities. This study employed a Classroom Action Research (CAR) design, which was conducted in two cycles involving 20 Grade V students as the research subjects. The data were collected through tests, observations, questionnaires, and documentation. The collected data were analyzed using descriptive qualitative and quantitative techniques. The results of the study indicated that the implementation of the Think Talk Write (TTW) learning model successfully improved students' explanatory text writing skills. The percentage of students achieving mastery increased from 30% in Cycle I to 90% in Cycle II. Teacher activity improved from 61.87% to 91.87%, while student activity increased from 69.37% to 91.25%. Furthermore, students' responses toward the implementation of the TTW learning model were highly positive, with 47.5% of students strongly agreeing, 50% agreeing, 2.5% disagreeing, and 0% strongly disagreeing. Therefore, it can be concluded that the Think Talk Write (TTW) learning model is effective in improving the explanatory text writing skills of Grade V students at UPTD SD Negeri 27 Peusangan